FAKTOR-FAKTOR PENENTU PERENCANAAN PEMBANGUNAN DESA DI DISTRIK AYAMARU UTARA KABUPATEN MAYBRAT PROVINSI PAPUA BARAT - Arne, Yunita; Pangkey, Masje Silija; Lengkong, Florence Daicy (JURNAL ADMINISTRASI PUBLIK, 2016)
ABSTRACT: This study originated from the initial observation in several villages in the area ofthe District of North Ayamaru Maybrat Regency, West Papua Province showed that the success rate ofrural development in this region is still very low terkategori, where most people categorized poor orunderprivileged families. This indication shows that the implementation of rural development has notbeen based on an effective rural development planning. Thus, this study aims to (1) To determine theeffectiveness of rural development planning; (2) To analyze whether the factor of leadership andcultural values also determine the effectiveness of rural development planning; and (3) To measure thesize of the contribution factor of leadership and cultural value to the effectiveness of rural developmentplanning in the District of North Ayamaru Maybrat Regency, West Papua Province.The design used inthis research is the design of diagnostic analytic, by applying descriptive-quantitative method. Samplesdrawn by purposive sampling of respondents as many as 36 employees / service personnel, then spreadQuestionnaire (a questionnaire) and the results are analyzed by applying descriptive statistical analysistechniques and partial regression analysis and multiple regression as well as product momentcorrelation and multiple correlation.The research results presented as follows: (1) The average achievements of the effectiveness ofrural development planning in the District of North Ayamaru Maybrat district is in the category of"low" likely to "moderate". Government leadership and cultural values together (simultaneously)make a positive contribution to the achievement of the effectiveness of rural development planning,particularly in the district of North Ayamaru Maybrat district. (2) Leadership village administrationin the category of "low" tend to "moderate". Partially, the leadership of the village administration haspositive influence on the achievements of the effectiveness of rural development planning, particularlyin the district of North Ayamaru Maybrat district. (3) The value of culture is in the category of "low"likely to "moderate" or sufficient. Partial cultural values or cultural village government organizationspositive effect on the achievements of the effectiveness of rural development planning, particularly inthe district of North Ayamaru Maybrat district. Thus, it can be concluded that the governmentleadership and cultural values is a decisive factor attainment of the effectiveness of rural developmentplanning, particularly in the district of North Ayamaru Maybrat district.It is recommended that theorientation of the leadership of the village administration needs to be improved, in the sense thatshould be oriented towards transformational leadership style that emphasizes aspects of charismatic,creativity and innovation, while value-oriented organizational culture need results, not merely aprocess-oriented.Keywords : Effectiveness Village Development Planning, Leadership, Culture Value